The Effect of Preoperative Medications on Length of Stay, Inpatient Pain, and Narcotics Consumption After Minimally Invasive Transforaminal Lumbar Interbody Fusion. Issue 1 (February 2019) - Haws, Brittany E.; Khechen, Benjamin; Patel, Dil V.; Bawa, Mundeep S.; Guntin, Jordan A.; Cardinal, Kaitlyn L.; Wiggins, Adam B.; Singh, Kern
Abstract : Study Design: This is a retrospective cohort study. Objective: To determine the association between preoperative medications and length of stay, inpatient pain, and narcotics consumption after a minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Summary of Background Data: Previous studies have identified risk factors for increased length of hospital stay, inpatient pain, and narcotics consumption. However, little is known regarding the effects of preoperative medications on outcomes after spine surgery. Methods: A prospectively maintained surgical database of patients undergoing primary, single-level MIS TLIF was retrospectively reviewed. Preoperative medications taken within 30 days before surgery were recorded for each patient and categorized by medication type. Poisson regression with robust error variance was used to determine the association between preoperative medications and length of stay, pain scores, and narcotics consumption. Multivariate analysis was performed using a backwards, stepwise regression to identify independent risk factors. Results: In total, 138 patients were included in this analysis. On bivariate analysis, benzodiazepines were associated with longer hospital stays [relative risk (RR)=2.03; P =0.031]. Benzodiazepines (RR=3.71; P <0.001) and preoperative narcotics (RR=2.60; P =0.012) were risk factors for pain ≥7 on postoperative day 0. On multivariate analysis, benzodiazepines were an independent risk factor for prolonged stay. Benzodiazepines, narcotics, and nonsteroidal anti-inflammatories were identified as independent risk factors for increased postoperative pain. Conclusions: These results suggest that benzodiazepines are a risk factor for increased length of stay and postoperative pain after MIS TLIF. Preoperative narcotics and nonsteroidal anti-inflammatories were also identified as risk factors for postoperative pain though this did not lead to increases in narcotics consumption. Patients taking these medications should undergo more vigilant perioperative monitoring for adequate pain management. More work must be done to further elucidate the association between preoperative medications and postoperative outcomes after MIS TLIF.